Проектування та розробка наукового калькулятора - Максюта, Роман Олегович; Maksyuta, Roman Olehovych (Ірпінь, 2024)
Розробка програмного забезпечення наукового калькулятора Завдання, які були виконання для досягнення визначеної мети: проаналізовано теоретичні аспекти розробки наукового калькулятора; сформовано вимоги до функціоналу та дизайну онлайн- калькулятора; здійснено аналітичний огляд технологій розробки програмного забезпечення онлайн калькулятора; здійснено аналітичний огляд існуючих конструкторів онлайн калькулятора;виконано практичну реалізацію онлайн калькулятора.

Development of scientific calculator software Tasks that were performed to achieve the specified goal: the theoretical aspects of the development of a scientific calculator were analyzed; the requirements for the functionality and design of the online calculator were formed; an analytical review of online calculator software development technologies was carried out; an analytical review of existing online calculator designers was carried out; the practical implementation of the online calculator was completed.
Design and development of a scientific calculator
Keywords: веб-розробка; онлайн калькулятор; програмне забезпечення; конструктор; фреймворки; web development; online calculator; software; designer; frameworks